A LOGISTIC APPROACH TO SHORTEN LEAD TIMES IN COURTS OF LAW – A CASE STUDY - Martins, A.; Helgheim, B.; Crespo de Carvalho, J. (Proceedings of the 19th Nofoma conference, 2007)
The Court System is often criticized for not performing at its best. Cases take longer than expected. Research based on the Theory of Constraints and Logistics took place in order to overcome these difficulties. The purpose of this paper is to identify the reasons why civil cases do not flow through the court system as announced in the Civil Code, and to discuss ways to shorten lead-times in the court process. A comparative analysis of two case studies, with a total of six court departments and a representative sample of 299 civil summary cases is used. The case studies and the court departments are independent variables and the 28 activities in the process are the dependent variables. The unit of analysis is the time spent in each activity. Two levels of analysis are used; one considering the total period of time a case remains in each activity, the second considering the delays in each activity. Quantitative data is analysed using statistical computation and findings are adjusted with qualitative data. Findings show that logistics concepts can be applied to the court system; and although the judge staff and the judge are the main constrains in the system, others such as the courtrooms may emerge if ill managed. Recommendations to shorten lead-times are provided.